Exploring the meaning of living with HIV as a chronic illness in Kenya: A narrative inquiry. (6th January 2017) - Maina, Geoffrey; Caine, Vera; Mill, Judy; Wimmer, Randolph
Abstract : Since the introduction of antiretroviral medications, HIV has been regarded as a chronic illness. However, people living with HIV continue to experience social consequences of HIV infection such as stigma, discrimination, violence, and other human rights violations. In this paper, we focus on the experiences of Atoti, a person living with HIV in Kenya. We argue that HIV remains a biographically disruptive and exceptional illness that is complicated by its invisibility and unpredictable trajectory. Based on Atoti's experiences, we argue that Bury's (1982) concept of biographical disruption, used to explain the social processes of a person suffering a chronic illness, does not fully capture the complexity of experiencing living with HIV. Focusing on life as a whole, rather than on the disease response and process as a biographical disruption, allows for a deeper appreciation of HIV's complexity as a medical illness with major social ramifications.